Pengujian Efektivitas Jenis dan Konsentrasi Zpt Terhadap Keberhasilan Stek Batang Tanaman Anggur (Vitis Vinifera L.) Varietas Jestro AG5 - Rudi Riyanto; Rommy Andhika Laksono; Yayu Sri Rahayu (Jurnal Ilmiah Wahana Pendidikan, 2022)
The experiment was carried out at the Screen House, Faculty of Agriculture, Singaperbangsa University, Karawang, which is located in Pasir Jengkol Village, Majalaya District, Karawang Regency, West Java. The design used was an experimental one-factor Randomized Block Design (RAK) with 3 replications. There were 10 treatments, namely A (Control), B (Atonik 1 ml/L water), C (Atonik 1.5 ml/L water), D (Atonik 2 ml/L water), E (Onion Extract 10 ml/L water ), F (OnionExtract 15 ml/L water), G (Onion Extract 20 ml/L water), H (Bean sprout Extract 10 ml/L water), I (Bean sprout Extract 15 ml/L water), J ( Sprout Extract 20 ml/L water). In testing the effectiveness of the type and concentration of ZPT on the success of grape stem cuttings (Vitis vinifera L.) Jestro Ag5 variety did not have a significant effect on the time of shoot emergence, number of shoots, number of leaves and root length. However, it has a significant effect on shoot length, root weight and root volume. Treatment C tended to give the best results on the observation parameters of the number of shoots 7 mst and 8 mst of 28.27 cm and 32.06 cm, respectively. Meanwhile, on the parameters of root weight and root length, treatment B gave the best effect of 22.27 g and 14.17 ml, respectively.